Investigating the diet of Mesolithic groups in the Southern Alps: An attempt using stable carbon and nitrogen isotope analyses - Valentina Gazzoni; Gwenaëlle Goude; Giampaolo Dalmeri; Antonio Guerreschi; Elisabetta Mottes; Franco Nicolis; Fabrizio Antonioli; Federica Fontana (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Stable isotopic data (δ13C; δ15N) were obtained from Mesolithic human and faunal remains from north- eastern Italy in order to document the human diet and provide information on the relationship between landscape use and subsistence strategies. The bone samples were from an adult female individual (Early Mesolithic, Late Sauveterrian) buried at Vatte di Zambana (Trento), an adult male (Late Mesolithic, Castelnovian) buried at Mondeval de Sora (Belluno), and an adult female from Mezzocorona Borgonuovo (Trento). For the latter, the stratigraphic position of the burial pit and evidence of the associated ritual suggest a Mesolithic attribution. Carbon (13C/12C) and nitrogen (15N/14N) stable isotope compositions of human bone collagen were compared with those of animal remains from different taxa found in stratigraphic association with the burial. The isotopic data and the Bayesian model developed from the latter and from data in the literature indicate a very significant proportion of terrestrial resources in the protein fraction of the human diet, particularly from red deer compared to other ungulates and potentially from freshwater fish and small mammals. These results add to the information provided by zooarchaeological studies and reopen the debate on the role of secondary resources such as chamois, ibex, small mammals and fish, such as pike, in the diet of these mobile human societies. However, as this is a preliminary study based on a very small sample size, interpretations should be considered with caution.